Article Commentary: Sex- and Gender-Based Medicine: The Need for Precise Terminology. Issue 3 (September 2017) - Madsen, Tracy E.; Bourjeily, Ghada; Hasnain, Memoona; Jenkins, Marjorie; Morrison, Mary F.; Sandberg, Kathryn; Tong, Iris L.; Trott, Justina; Werbinski, Janice L.; McGregor, Alyson J.
As our knowledge of sex- and gender-based medicine (SGBM) continues to grow, attention to precision in the use of related terminology is critical. Unfortunately, the terms sex and gender are often used interchangeably and incorrectly, both within and outside of the typical binary construct. On behalf of the Sex and Gender Women's Health Collaborative (SGWHC), a national organization whose mission is the integration of SGBM into research, health professions education, and clinical practice, our objective was to develop recommendations for the accurate use of SGBM terminology in research and clinical practice across medical specialties and across health professions. In addition, we reviewed the origins and evolution of SGBM terminology and described terms used when referring to individuals outside the typical binary categorization of sex and gender. Standardization and precision in the use of sex and gender terminology will lead to a greater understanding and appropriate translation of sex and gender evidence to patient care along with an accurate assessment of the impact sex and gender have on patient outcomes. In addition, it is critical to acknowledge that SGBM terminology will continue to evolve and become more precise as our knowledge of sex and gender differences in health and disease progresses.